Prevalence and Genotype Distribution of Human Papillomavirus Infection Among 40,613 Women: An Outpatient-Based Population Study in Kunming, Yunnan - Zhang, Yu; Xu, Ya; Dian, Ziqin; Zhang, Guiqian; Fan, Xin; Zhao, Yuan; Sun, Yi (Frontiers in Public Health, 2022)
Human Papillomavirus (HPV) infection is one of the most common sexually transmitted infections worldwide. This study aimed to investigate the prevalence and genotype distribution of HPV among the outpatients from gynecology or reproductive gynecology clinics and physically examined population in the Yunnan Province. A total of 40613 women were recruited from the First People’s Hospital of the Yunnan Province. Our study findings showed that there were significant differences in the prevalence of HPV among various populations. The prevalence of HPV in gynecological outpatients was the highest, while the prevalence was the lowest among women seemingly healthy who underwent physical examinations. The predominant form of HPV infection was a single infection, and there was a large overlap in the distribution of the most prevalent subtypes among various populations. The three most common high-risk subtypes were HPV-52, 16, and 58 in our study population. Moreover, the prevalence of HPV peaked in the age groups of less than 25 years and over 55 years. Our study on the epidemiology of HPV among various populations will provide scientific evidence for the prevention and control plans of cervical cancer in Yunnan Province.